2020
DOI: 10.1039/d0ee02230f
|View full text |Cite
|
Sign up to set email alerts
|

High energy density anodes using hybrid Li intercalation and plating mechanisms on natural graphite

Abstract: A novel Li-Ion battery anode is presented which leverages the good performance of industrial graphite anodes and enhances their performance by allowing for reversible Li plating on their surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The oxidation peaks at around 0.53 V correspond to the Li dealloying process of the Li-Si phases to Si domains. [26] The SiNWs@ RGO electrode exhibited excellent electrochemical performance owing to its unique structure. The self-supporting electrode charge-discharge curve of SiNWs-76 (Figure 4a) showed that SiNWs-76 exhibited an initial charge capacity of 3484.3 mAh g −1 with an ICE of ≈89.5% (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation peaks at around 0.53 V correspond to the Li dealloying process of the Li-Si phases to Si domains. [26] The SiNWs@ RGO electrode exhibited excellent electrochemical performance owing to its unique structure. The self-supporting electrode charge-discharge curve of SiNWs-76 (Figure 4a) showed that SiNWs-76 exhibited an initial charge capacity of 3484.3 mAh g −1 with an ICE of ≈89.5% (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, representative values whose cycling number is over 100 in the literature were included in the plot, and the number of cycles is also specified. The literature values were categorized into five different groups—porous scaffolds made of carbonaceous materials [ 33,46–53 ] (blue triangles in Figure 5d) and metals [ 16,19,54–61 ] (orange inverse triangles), porous scaffolds whose separator side is covered by coating layers, [ 15,22,62,63 ] (similar to our LM‐CNT configuration) (green diamonds), lithium metal covered by polymeric [ 23,25,64–69 ] (yellow green squares), or ceramic materials [ 70–72 ] (pink circles). As for metal‐based and carbon‐based scaffolds, lithiophilic materials (Au, [ 55 ] CuO, [ 17,56,57 ] MnO 2 , [ 48 ] ZnO, [ 59,61 ] Si [ 33 ] ) were often decorated in the pores to alleviate lithium clogging near the inlet of the pores during lithium plating.…”
Section: Resultsmentioning
confidence: 99%
“…133 The intermetallic interphase concept is apparently well suited for this new design to regulate the Li deposition behavior. 134 However, it should also be realized that we are still inconclusive about the more fundamental working mechanisms behind many of the successful demonstrations. For instance, lower reactivity against the electrolyte, reduced nucleation barrier, better surface chemistry uniformity, faster surface Li + diffusion, improved charge transfer of Li + at the LMA-electrolyte interface, and so forth.…”
Section: Discussionmentioning
confidence: 99%